Bruises, abrasions, and scars in children aged 4-14 years in Denmark : A comparison between police-reported cases of physical child abuse and a control group - Slot, Liselott; Thorlacius-Ussing, Lykke; Justesen, Daniella; Bugge, Anne Birgitte Dyhre; Lynnerup, Niels; Wingren, Carl Johan; Banner, Jytte (Journal of Forensic Sciences, 2025)
Differentiating between abusive and accidental skin lesions in children presents significant challenges. Previous studies of skin lesion patterns have mainly focused on bruises in younger children. In this study, we compare the number, location, and distribution of recent (bruises and abrasions) and older (scars) skin lesions between police-reported cases of physical violence and controls of similar age (4-14 years) in a Danish setting. The study included 262 cases and 119 controls. Skin lesions in 19 body regions were assessed. Univariate and multivariate logistic regression models were conducted including body regions, age group, sex, and activity level. Having scars on the buttocks was conclusively associated with the case group (OR: 5.0; 95% CI: 1.5-17). There was a tendency for cases to have more scars on the upper arms, hands, lower parts of the back (midline), and legs. We did not find an association between recent skin lesions (bruises and abrasions) and physical violence. A difference in activity levels between cases and controls may explain the higher number of recent lesions in the control group. It is crucial to promptly examine children exposed to violence. If this is not possible, examining for older skin lesions remains important.
© 2025 American Academy of Forensic Sciences.